Panorama and challenges of postgraduate education in pragmatic areas for the productive industries: Eengineering, Management, Economy and Accountancy - Sarmiento-Rojas, Jorge Andrés ; Universidad Pedagógica y Tecnológica de Colombia; Barreto Bernal, Patricia Carolina ; Universidad Pedagógica y Tecnológica de Colombia; Rojas Cruz, Diana Lizeth ; Universidad Pedagógica y Tecnológica de Colombia (UPTC Editorial, 2021)
The book presents the results obtained in a research study in which the trends of postgraduate offerings in Engineering, Management, Economics and Accounting in Africa, Asia, Europe, Latin America and two countries of the American continent, including United States and Colombia, were analyzed. Among the data obtained, the leading universities, the most offered programs and some comparative references on their labor possibilities and training needs to correspond to the relevance in the productive field were highlighted. The book concludes with some reflections and considerations about the implications of the pandemic for Higher Education and the challenges that the new scenario represents for Universities